Bronchiolitis obliterans - Kabir, MA; Hossain, SS; Dutta, BR (Mediscope, 2017)
The term ‘bronchiolitis obliterans’ was historically used by pathologists to refer to two distinct patterns of small-airway disease. The first was characterized by intraluminal polyps in the small airways. It was subsequently named bronchiolitis obliterans with organizing pneumonia and, more recently, cryptogenic organizing pneumonia. The second pattern was characterized by sub-epithelial inflammatory and fibrotic narrowing of the bronchioles, which is now recognized as obliterative bronchiolitis or constrictive bronchiolitis. In this study we reported a case of a male patient of 55 years who got admitted to a teaching hospital with progressive dyspnea and nonproductive cough over a period of 12 months and was released after proper treatment and management. Mediscope Vol. 4, No. 2: Jul 2017, Page 39-43